Improving Table Tennis Forehand Technique Using a Bounce Wall - Nasution, Usman; Purba, Martry Norayani; Rezeki, Annisa Diah Sri; Tarigan, Diego Zeusilus; Wahyudi, Wahyudi; Afwan Nst, Riyadi (CV. Rayyan Dwi Bharata, 2024)
The aim of this research is to determine the improvement of basic forehand techniques in table tennis using a rebound wall. The research method used in this research is descriptive research. Descriptive research is research that attempts to describe a symptom, event, incident that is happening now. Table tennis is a sport that knows no age limits. Children and adults can play together. It can be considered a recreational event, it can also be considered an athletic sport that must be taken seriously. But if we want to master table tennis as a sport, we have to learn and understand the various strokes available. We also have to master the various main playing styles. It is impossible for us to master table tennis well without knowing these basics. When learning table tennis, one of the techniques used is the forehand.